2012
DOI: 10.1016/j.ijid.2012.05.211
|View full text |Cite
|
Sign up to set email alerts
|

Frequent in-migration and highly focal transmission of dengue viruses among children in Kamphaeng Phet, Thailand

Abstract: e9015th ICID Abstracts / International Journal of Infectious Diseases 16S (2012) e2-e157 mild flu-like symptoms to bronchiolitis and severe pneumonia, and predisposes to the development of asthma. Preterm birth and pre-existing respiratory tract disorders increase risk of developing severe RSV infection. There is conflicting evidence about whether severe RSV disease is correlated to RSV genotype. Molecular epidemiological data from tropical Asia is relatively lacking. This study aims to identify the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The situation in rural areas, which make up the majority of the country, may be markedly different. Phylogenetic studies have shown widespread genetic and serotype diversity across the rural Thai province of Kamphaeng Phet with some clustering of lineages within villages [6], [7]. In addition, cluster studies in the same region detected infected individuals within 15 days of an index case at distances of 100 m within villages [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The situation in rural areas, which make up the majority of the country, may be markedly different. Phylogenetic studies have shown widespread genetic and serotype diversity across the rural Thai province of Kamphaeng Phet with some clustering of lineages within villages [6], [7]. In addition, cluster studies in the same region detected infected individuals within 15 days of an index case at distances of 100 m within villages [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…; Rabaa et al. ). It is unlikely that A. albopictus , a secondary DENV vector found in Thailand, prevented local adaptation because A. aegypti is the predominant mosquito vector at our study sites (Chareonviriyaphap et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Rabaa et al. ). While there is compelling evidence for genetic differences in virulence and epidemic potential among DENV genotypes, lineages, and strains (Rico‐Hesse ), the evolutionary forces that shape the spatial structure of DENV genetic diversity presently are not fully understood.…”
Section: Introductionmentioning
confidence: 97%
“…We could not find any studies done on factors associated with internal migration among dengue patients from other studies. Although there is evidence that migrant workers had more risk of dengue (3)(4)(5), probably due to residing in poor housing conditions. Therefore, a comparative study would be recommended for assessing the association between risks of dengue infection and residing in poor housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the migration status of the patients from dengue non-endemic areas to endemic areas is thought to be a risk factor, of which the epidemiology is poorly understood. Research evidence suggests that internal migrant workers are more vulnerable to dengue (3)(4)(5). However, the underlying determinants for their vulnerability to dengue has not been explored in depth.…”
Section: Introductionmentioning
confidence: 99%